2012
DOI: 10.1590/s1516-35982012000500006
|View full text |Cite
|
Sign up to set email alerts
|

Biomass accumulation in mombasa guineagrass plants under different levels of nitrogen supply and plant densities

Abstract: -The objective of this study was to evaluate the effect of different levels of nitrogen supply and plants densities in the productivity of mombasa guineagrass (Panicum maximum) in the period of establishment. The design was of completely randomized blocks, with 12 treatments and three repetitions, with four nitrogen supplies (absence of application, 80, 160 and 320 kg/ha.year) and three plant densities (9, 25 and 49 plants/m²). The plot was cut at 30 cm from the ground when the sward high intercepted 95% of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Megathyrsus maximus) presents one of the greatest potential production of dry matter (DM) in subtropical and tropical environments that are known and can reach annual production of dry matter around 33 t ha -1 . Proper management of soil fertility and knowledge of the nutritional requirements of this grass are extremely important to the practice of pasture management, which reflects in higher productivity and availability of food for the animals (Euclides et al, 2007;Silva et al, 2009;Barth Neto et al, 2010;Silveira et al, 2010;Pereira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Megathyrsus maximus) presents one of the greatest potential production of dry matter (DM) in subtropical and tropical environments that are known and can reach annual production of dry matter around 33 t ha -1 . Proper management of soil fertility and knowledge of the nutritional requirements of this grass are extremely important to the practice of pasture management, which reflects in higher productivity and availability of food for the animals (Euclides et al, 2007;Silva et al, 2009;Barth Neto et al, 2010;Silveira et al, 2010;Pereira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also responsive to higher input conditions and also suitable for cultivated/irrigated conditions. The species is highly responsive to fertilizers, which results in an increased number of cuts of the grass (Pereira et al, 2012). Despite the latter information and being considered to be shade tolerant, some studies had reported different results.…”
mentioning
confidence: 99%
“…The fodder presents 11.6% of crude protein (CP), 68.6% of soluble neutral detergent fiber (NDF) and 41.1% of soluble acid detergent fiber (ADF) (Molina et al, 2015), and degradability of the dry matter of 47% (Almaraz-Buendía et al, 2019). However, factors such as the season of the year and the population density of plants affect the yield and nutritional quality of the grasses (Freitas et al, 2012;Pereira et al, 2012). In a study it was observed that the Guinea grass presented better chemical composition in the early rainfall season, followed by the winter season, and the worst chemical composition in the dry and late rainfall season ( Juárez et al, 2009); for their part, Muñoz-González et al (2016) reported that the chemical composition was better in the dry season.…”
Section: Introductionmentioning
confidence: 99%